Dampak Teknologi Smartphone Dalam Pemenfaatan Service Bank - sasa ani arnomo (Universitas Putera Batam, 2014)
Development of smartphones in Indonesia change the order of the marketing strategy in which the public interest is increasing to transact online without having to transact face to face (face to face). Changes towards online transactions also affect transactions in the banking industry. Service bank was developed to meet customer satisfaction include SMS banking and internet banking. With the existence of such services is expected to facilitate the effective and efficient transaction. Sophistication smartphone influential enough to service bank through the application of gadgets or ease of access intenet. From the description of this study is to see how the impact of the use of smartphone technology service bank. The method used is quantitative method by using statistical techniques. Primary data were collected through questionnaires to 158 respondents using incidental sampling technique wherein the determination technique based on chance. The description of the use of smartphones, SMS banking and interest in the use of e-banking presented through quantitative descriptive analysis. The results of quantitative descriptive analysis shows that the use of smartphones has been optimized, sms banking has been going well and the use of e-banking interests perceived high. The results of the analysis revealed that the development of smartphones have a positive impact on the utilization of bank service excellent views of internet banking or SMS banking.